Elaboración de un manual del proceso de contratación privada del condominio Alejandro Magno ubicado en el km 14,5 vía Samborondón considerando su sistema constructivo, especificaciones técnicas, presupuesto y programación de obra - Arias Montoya, Julio Andrés (2017)
Due to the great need of knowledge about the legal and social processes of the private contracting and the elaboration of a contract with their respective rights and obligations, clauses for the construction of condominiums has to implement a strategy that increases the knowledge in this subject to the citizenship. Considering the need to have a written agreement for the execution of a work, which helps the contracting parties in their relationship Contractor and Contractor, to be able to execute the work according to what is written in the contract will serve as a guide during its execution, As a pattern to follow at the same time will have rights and obligations to fulfill during the execution of the work………